تاثير قيمة العلامة التجارية على قرار الشراء لدى المستهلك الجزائري - جباري مسعودة; نويوة نور الهدى; د/ تربح محمد (جامعة عمار ثليجي الاغواط, 2024)
ملخص الدراسة: هدفت الدراسة الحالية إلى معرفة العالقة بين الضغط النفسي و قلق الامتحان لدى تلاميذ السنة الثالثة ثانوي، بالإضافة إلى التعرف على العالقة بين الضغط النفسي وقلق الامتحان، والكشف عن الفروق في على متغيري الجنس والتخصص ً هذه العالقة بناء .المختار فرضيات الدراسة، تم استخدام المنهج العلائقي ، وتم تطبيق الدراسة على عينة عشوائية طاقية ً وتلميذة. أما أدوات الد ارسة، فقد تم استخدام مقياس الضغط النفسي المدرسي لبوقات مكونة من 31 تلميذا 2102 ومقياس قلق الامتحان لغربي )2102(. وتم التأكد من الخصائص السيكو متريةللأداتين، ولتحليل ً تم استخدام اختار )ت( لعينة واحدة، المتوسط الحسابي، النحس ارف المعياري، معامل البيانات إحصائيا الارتباط بيرسون، ومعادلة دالة الفرق بين معاملاتالارتباط، وذلك باستخدام برنامج الحزمة الإحصائية اسفرت الدراسة على النتائج التالية : ال توجد فروق ذات داللة احصائية للضغط النفسي في ظل متغير الجنس لدى أفراد العينة ال توجد فروق ذات داللة احصائية لدرجة القلق في ظل متغير الجنس لدى عينة الدراسة ال توجد فروق ذات دالة احصائية للضغط النفسي وقلق الامتحان في ظل متغير السن لدى أف ارد العينة تم تفسير نتائج الفرضيات على ضوء الإطار النظري ومجموعة من الد دارسات السابقة الكلمات المفتاحية: الضغط النفسي، ، قلق الامتحان، تلاميذ السنة الثالثة ثانوي StudySummary : The main propose of this article is to provider information on the importance of the Islamicfaith and the importance of the Islamicfaith in the Islamic world, The Prophet Muhammad (peace and blessings of Allah beuponhimsaid: "I am the one who has the power to makepeacewith Allah and His people. The company has a large number of employees, including the director of the company, and the director of the company, whowillberesponsible for the production of 130 million copies. The author of the book, Theodore Roosevelt, wasbornin 1942 in New York City (2012) and died in New York City (2015). And the people of the country are very happy, and the people of the country are very happy () withtheirfamilies and friends, theirfamilies, theirfamilies, theirfamilies The latest version of the SPSS 25.0 software, including the latest version of the SPSS 25.0 software, isavailablein 25 languages. The islamiccalendar of the month of july: We are going to have a good time in the month of july, and wewill have a good time in the month of julyWe are going to have a good time in the month of july The islamic world is a place where the islamic world is a place where the islamic world is a place where the islamic world is a place where the islamic world is a place The sultanate of the sultanate of the sultanate of the sultanate of the sultanate of the sultanate. ,The main purpose of the project: to prepare a mea
دراسة استطلاعية على مستخدمين الهواتف الذكية